An m5C methylation regulator-associated signature predicts prognosis and therapy response in pancreatic cancer - Yun, Duo; Yang, Zhirong; Zhang, Shuman; Yang, Hai; Liu, Dongxue; Grützmann, Robert; Pilarsky, Christian; Britzen-Laurent, Nathalie (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is the most aggressive digestive malignancy due to frequent late-stage diagnosis, rapid progression and resistance to therapy. With increasing PDAC incidence worldwide, there is an urgent need for new prognostic biomarkers and therapy targets. Recently, RNA methylation has emerged as a new tumorigenic mechanism in different cancers. 5-methylcytosine (m5C) is one of the most frequent RNA modifications and occurs on a variety of RNA species including mRNA, thereby regulating gene expression. Here we investigated the prognostic role of m5C-regulator-associated transcriptional signature in PDAC. We evaluated m5C-regulator status and expression in 239 PDAC samples from publicly available datasets. We used unsupervised consensus clustering analyses to classify PDACs based on m5C-regulator expression. From the resulting signature of differentially expressed genes (DEGs), we selected prognosis-relevant DEGs to stratify patients and build a scoring signature (m5C-score) through LASSO and multivariate Cox regression analyses. The m5C-score represented a highly significant independent prognostic marker. A high m5C-score correlated with poor prognosis in different PDAC cohorts, and was associated with the squamous/basal subtype as well as activated cancer-related pathways including Ras, MAPK and PI3K pathways. Furthermore, the m5C-score correlated with sensitivity to pathway-specific inhibitors of PARP, EGFR, AKT, HER2 and mTOR. Tumors with high m5C-score were characterized by overall immune exclusion, low CD8+ T-cell infiltration, and higher PD-L1 expression. Overall, the m5C-score represented a robust predictor of prognosis and therapy response in PDAC, which was associated with unfavorable molecular subtypes and immune microenvironment.